Upaya Peningkatan Kemampuan Keterampilan Memukul Pada Permainan Bola Kasti Dengan Menggunakan Modifikasi Alat Bantu Pemukul dan Bola Pada Peserta Didik Kelas VI Sekolah Dasar Negeri Gading 1 Surabaya - Yusril Wibowo Febriyanto; Doni Andrijanto; Feri Johanis (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
PE learning in schools will be optimal if the available facilities and infrastructure are adequate and the learning process focuses on the needs of students, of course, on the kasti ball game material. There are several factors that are obstacles, namely from the students themselves such as fear in doing blows, lack of confidence. This study aims to determine the effect of the modification of hitting aids and balls on the ability of hitting and throwing skills in the game of kasti ball for grade 6 students of SDN Gading 1 Surabaya. Data collection was carried out through student skill tests by providing modifications to batting aids and balls to determine the improvement of hitting skills in students. Data analysis uses descriptive statistical tests in the form of averages, standard deviations, variances, and inferential statistics using normality tests, t-tests, and improvement measurements. Based on the results of the study, it was shown that there was an increase in the ability of hitting skills in the game of kasti ball by more than 90% after being given modifications of batting aids and balls to students.